BUILDING RESILIENT AND SCALABLE PAYMENT GATEWAYS FOR THE FUTURE - Puneet Chopra; Ankur Binwal (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
As digital transactions dominate the global financial landscape, the need for robust, scalable, and secure payment gateways has never been more critical. This article explores the key considerations and challenges in designing and implementing payment gateways that can handle high transaction volumes, ensure low latency, and maintain compliance with evolving global financial regulations. The article reveals that modern payment infrastructures must process volume surging to over 40,000 transactions per second during peak periods while maintaining processing times under 100 milliseconds. The article demonstrates that implementing distributed architectures and cloud-native technologies can reduce infrastructure costs by up to 45% while achieving 99.99% uptime. Advanced security measures, including AI-powered fraud detection systems, have shown accuracy rates of up to 99.9%, significantly outperforming traditional rule-based systems. The integration of blockchain technology has demonstrated potential for reducing cross-border transaction costs by 60% while enabling settlement times of 3-5 seconds compared to traditional 3-5 day periods. The article delves into architectural strategies, emerging technologies, and best practices that contribute to building resilient payment infrastructures capable of meeting the demands of the modern digital economy, where the global digital payments market is projected to reach 180.4 billion by 2026, growing at a CAGR of 15.2%.